2013
DOI: 10.1517/17460441.2013.788495
|View full text |Cite
|
Sign up to set email alerts
|

Repairing mutated proteins – development of small molecules targeting defects in the cystic fibrosis transmembrane conductance regulator

Abstract: Although the development of CFTR-targeting agents has little access to structural information from crystal structures, several promising compounds have been discovered so far. Advanced virtual models of CFTR and high-throughput assays have helped the developmental programs. While Ivacaftor, the first of the CFTR potentiators, has now reached clinical use, CFTR corrector development has not been successful thus far. However, intense research of the mutation F508del, the mutation considered the most frequent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Cystic fibrosis (CF) is the most common genetic (autosomal recessive) disease in Caucasians, with an estimated 80,000 CF diagnosed cases worldwide ( Lubamba et al, 2012 ; Hanrahan et al, 2013 ; Merk and Schubert-Zsilavecz, 2013 ; De Boeck et al, 2014 ). Current strategies for treatment of CF patients can be broadly divided into two main categories: agents that target downstream effects of Cystic Fibrosis Transmembrane conductance Regulator (CFTR) dysfunction (i.e., symptomatic treatment) and agents that target the root cause of the disease, i.e., CFTR modulators which address the absent or dysfunctional CFTR in epithelial membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Cystic fibrosis (CF) is the most common genetic (autosomal recessive) disease in Caucasians, with an estimated 80,000 CF diagnosed cases worldwide ( Lubamba et al, 2012 ; Hanrahan et al, 2013 ; Merk and Schubert-Zsilavecz, 2013 ; De Boeck et al, 2014 ). Current strategies for treatment of CF patients can be broadly divided into two main categories: agents that target downstream effects of Cystic Fibrosis Transmembrane conductance Regulator (CFTR) dysfunction (i.e., symptomatic treatment) and agents that target the root cause of the disease, i.e., CFTR modulators which address the absent or dysfunctional CFTR in epithelial membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Several classes of CFTR potentiators have been reported (Figure ) such as flavones (genistein), chromen-4-ones (UC CF -29), sulfonamides (SF-01), phenylglycines (PG-01), and our previously described pyrazoles (VRT-532). , It is speculated that these molecules interact directly with the nucleotide binding domain region of CFTR . However, many of these compounds display low potency, limited selectivity, and poor pharmacokinetic properties in preclinical species, making them unsuitable for development as human therapeutics .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the F508del mutation perturbs the native interactions between NBD1 and the coupling helix of MSD2 . The breakthrough finding was that misfolding of the defective F508del‐CFTR could be corrected by lowering the temperature (<30°C) or by employing chemical chaperones (e.g., glycerol) . For the first time, this indicated that defective CFTR function could be restored; this in turn led to extensive efforts by Vertex to identify small‐molecule CFTR modulators .…”
Section: Mode Of Actionmentioning
confidence: 99%
“…The breakthrough finding was that misfolding of the defective F508del‐CFTR could be corrected by lowering the temperature (<30°C) or by employing chemical chaperones (e.g., glycerol) . For the first time, this indicated that defective CFTR function could be restored; this in turn led to extensive efforts by Vertex to identify small‐molecule CFTR modulators . Mechanistically, CFTR modulators fall into three classes: 1) suppressors that prevent premature termination of protein synthesis (i.e., ataluren); 2) correctors that partially correct folding and processing defects (i.e., lumacaftor); and 3) potentiators that increase channel gating and conductance (i.e., ivacaftor).…”
Section: Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation